X-ray magnetic circular dichroism on La2/3Ca1/3Mn0.97Fe0.03O3 thin films (2015)
The element-selective technique of X-ray magnetic circular dichroism (XMCD) has been used to study the magnetic properties of La2/3Ca1/3Mn0.97Fe0.03O3 (LCMFO) thin films. XMCD measurements below the ferromagnetic ordering temperature at the Mn and Fe absorption edges allow the determination of the contributions and relative orientations of the Mn and Fe magnetic moments. A reduction in the Mn XMCD signal of the LCMFO sample compared to that for the parent La2/3Ca1/3MnO3 (LCMO) system reveals important modifications in the electronic and magnetic properties with the presence of Fe. The Fe X-ray absorption (XAS) for the LCMFO film is characteristic of Fe3+, and the comparison with multiplet calculations shows that the Fe dopants occupy octahedral sites in the crystal, which is consistent with Fe3+ substituting Mn3+ in LCMO. The magnetic moments of Mn and Fe are found to align antiparallel, which suggests the presence of Mn–O–Fe superexchange coupling. This result is consistent with macroscopic magnetometry measurements on the LCMFO system, which show a decrease in saturation magnetization of LCMO with Fe doping.